COVID 19 Forced cancelation of Uluwatu Cliff’s Fortification - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2020)
Badung Regency Government forced to postpone several projects in 2020 due to COVID-19 pandemic. Uluwatu temple, a gem in Bali's southern part, became one of many sites that need to be maintained. Above all, a viral photo about the Uluwatu cliff in 2019 made the public's attention focused on the iconic tourism spot. The circulated image depicted a massive crack on the rocky height at the side of the Uluwatu temple. The Manager, I Wayan Wijana, admitted that there is a crack on cliffs at Uluwatu Temple. Furthermore, it has been there for decades. According to observers, in 1992, there was an insignificant decrease of about one millimeter. Although Uluwatu cliff's crack has been there for decades, there was no significant government action. Local authorities decided to reduce the number of prayer visits during ceremonies and center tourism activities in the outer temple area to prevent any accidents. Besides, the Badung regency government had conducted few patches on the cliffside, with a regular annual inspection. Finally, In 2019, the Government of Badung invited potential quotation to fortify the Temple's base. Nevertheless, there was no final announcement regarding the quotation winner. In the second quarter of 2020, Badung Public Works and Spatial Planning Agency announced a temporary suspension on several infrastructure projects due to budget allocation for COVID-19 handling. The announcement confirmed that the Uluwatu fortification project would not be conducted in the year.